Relationship Between Reemployment Intention, Job Performance, and Job Satisfaction Among College Interns - Chang, Yun-Hsi (Journal of advanced computational intelligence and intelligent informatics, 2025)
This study aimed to examine the relationship between interns’ job satisfaction, job performance, including professional competence and teamwork performances, retention intention, and managers’ willingness to reemploy interns after graduating from internship programs and universities. A quantitative questionnaire survey method was adapted in this study. A total of 317 participants were recruited for a 24-item pilot questionnaire, and 329 valid formal questionnaires were confirmed for analysis using descriptive statistics, difference testing, and regression analysis. Then, there were five research major findings, and some implications and practical suggestions of the research were discussed.